RANCANGAN PENGUKURAN KINERJA DENGAN BALANCE SCORECARD PADA SISTEM MANAJEMEN STRATEGI - Malikul Adil (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Balance Scorecard represent a group of integrated performance measuring rod coming from company strategy from entire/all part of organization. Basically strategy represent a theory about how to reach the target of organization. In approach of Balance top management scorecard formulate its strategy into performance measuring rod, so that employees comprehend and can execute something to reach the strategy. Balanced Scorecard represent a strategic management system or more precise named by: “ Based system accounting responsibility Strategic” what formulate strategy and mission an organization into target of performance measuring rod and operational to 4 different in perspective, that is is in perspective financial, in perspective customer, in perspective of internal business process and is in perspective of growth and learning